2014
DOI: 10.1038/ki.2013.340
|View full text |Cite
|
Sign up to set email alerts
|

Toward a working definition of C3 glomerulopathy by immunofluorescence

Abstract: Precise immunofluorescence criteria for C3 glomerulopathy remain to be defined. Here we tested hierarchical immunofluorescence criteria with varying stringency for C3 glomerulopathy in a cohort with dense deposit disease as the gold standard and then applied these criteria to analyze the incidence of C3 glomerulopathy in membranoproliferative glomerulonephritis (MPGN) types 1 and 3. Among 319 archived cases of primary MPGN types 1-3, immunofluorescence reports were retrospectively coded as glomerular deposits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
164
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 23 publications
(24 reference statements)
2
164
0
7
Order By: Relevance
“…To our knowledge, the effect of eculizumab on leukocyturia in DDD GN has previously not been described. Although leukocyturia is not commonly reported as a presenting symptom in DDD (8,9,28), it was a consistent finding in all patients with urinary leukocyte counts available. In the absence of other causes of leukocyturia, the fact that leukocyturia disappeared almost completely and within 1 week after the first dose in all episodes of GN with leukocyturia strongly indicates a direct effect of eculizumab.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, the effect of eculizumab on leukocyturia in DDD GN has previously not been described. Although leukocyturia is not commonly reported as a presenting symptom in DDD (8,9,28), it was a consistent finding in all patients with urinary leukocyte counts available. In the absence of other causes of leukocyturia, the fact that leukocyturia disappeared almost completely and within 1 week after the first dose in all episodes of GN with leukocyturia strongly indicates a direct effect of eculizumab.…”
Section: Discussionmentioning
confidence: 85%
“…2 Although the original concept was based on the presence of isolated C3 it is clear that, in practice, this is too stringent a definition and that, if cases where the underlying pathology is alternative pathway activation are not to be missed, a wider net is needed. This was clearly shown by a study from Hou et al 3 They looked at cases of dense deposit disease in which it is generally accepted that the glomerular changes result from abnormal control of the alternative pathway of complement. They found that if they used a stringent criterion of only C3 with no immunoglobulins then 50% of cases diagnosed as dense deposit disease on electron microscopy would not be classified as C3 glomerulopathy.…”
mentioning
confidence: 98%
“…However, a proportion of C3 glomerulopathy biopsies may show small amounts of Igs on immunofluorescence. 9,10 As a result, the definition of C3 glomerulopathy now states that C3 staining should be dominant and at least 2 orders of magnitude more intense than any other immune reactants. 8 This can lead to interobserver variability.…”
mentioning
confidence: 99%